Analysis of inflammasomes and CYP27B1 genes in cuprizone demyelinated C57BL/6 mice and evaluation of Th1 and Th2 patterns after oral administration of Lactobacillus casei strain T2 (IBRC-M10783). (June 2021) - Digehsara, Saeideh Gharekhani; Name, Niloofar; Sartipnia, Nasrin; Karim, Elahe; Taheri, Saba; Ebrahimi, Maryam Tajabadi; Arasteh, Javad
Abstract: Multiple sclerosis is characterized by the destruction of myelin in the CNS. Various factors including genetics, epigenetics, and environmental factors are involved in the development of the disease. There is evidence that changes in the gut microbiome profile are associated with immune-related diseases such as MS. Probiotics can alter the composition of the gut microbiota on the mucosal surfaces by differentiating naive T cells into Th1, Th2, Th17, and Treg cells. Female C57BL/6 mice were divided into 6 groups (n = 7): Normal group, cuprizone group (gavage of cuprizone for 4 weeks), Probiotic group (gavage of probiotic for 4 weeks), Treatment1 group (Probiotic for 4 weeks and then cuprizone for 4 weeks), treatment2 group (cuprizone for 4 weeks and then probiotic for 4 weeks) and treatment3 group (cuprizone for 4 weeks and then probiotic for 4 weeks with vitamin D3). Then the expression of NLRP-1, NLRP-3, AIM2, and CYP27B1 genes were evaluated using Real-Time PCR, and serum levels of IFN-γ and IL-4 were also measured by ELISA.The results showed a significant decrease in the expression of inflammasome and CYP27B1 genes in the probiotic-treated groups compared to the cuprizone group. Also, the comparison between probiotic-treated groups and cuprizone group showed a significant decrease in the amount of IFN-γ and IL-4. Due to reduced expression of the inflammasome genes as well as the decrease in IFN-γ levels as an inflammatory cytokine, it appears that L. casei may be effective in the healing process of demyelinated mice. Highlights: Cuprizone demyelinated C57BL/6 Mice. Lactobacillus casei strain T2 (IBRC-M10783). Effects of lactobacilli casei on IL-4 and IFN-γ production Th1 and Th2 patterns. Lactobacillus casei decreased AIM2, NLRP-1 and NLRP-3 expression. The effect of Lactobacillus casei on CYP27B1 gene expression.